Edukasi Gizi Seimbang dan Penguatan Partisipasi Ibu dalam Kegiatan Posyandu untuk Meningkatkan Status Gizi Balita - Ayu irawati; Susianti Susianti; Arifa Usman; Hijrah Hijrah (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
Balanced Nutrition Education and Strengthening Mothers' Participation in Posyandu Activities to Improve Toddler Nutritional Status Toddler nutrition continues to be a key focus in public health initiatives. Mothers' diet and active use of health services, particularly integrated health posts (Posyandu), are two factors that influence the nutritional status of toddlers. To help improve children's nutritional status, this community service project aims to strengthen mothers' involvement in Posyandu activities and raise their awareness of balanced nutrition. Thirty mothers of toddlers were targeted for this project, which was implemented in the Campalagian Community Health Center (Puskesmas) working area. Mothers were encouraged to actively participate in Posyandu activities through mentoring and education on balanced nutrition through counseling and interactive conversations. Mothers' attendance at Posyandu activities was monitored, and knowledge gains were measured using pre- and post-tests. The study found that mothers' average knowledge scores increased from 60 to 82, and mothers' attendance at Posyandu activities increased from 65% to 85%. This project demonstrates that balanced nutrition education and strengthening mothers' participation in Posyandu activities are effective in increasing mothers' knowledge and involvement, potentially supporting efforts to improve and prevent nutritional problems in toddlers on a sustainable basis.